PERTIMBANGAN PENYIDIK MENGHENTIKAN PROSES HUKUM TERHADAP PELAKU TINDAK PIDANA KECELAKAAN LALU LINTAS YANG MENGAKIBATKAN ORANG LAIN MENINGGAL DUNIA DI KEPOLISIAN RESOR KOTA PEKANBARU - David Binsar Ari Mangasi; Dessy Artina; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Structuring or changes to the rules on the highway is absolute considering the current rules of Traffic and Road Transport has been deemed incompatible with the development and needs of society as set forth in the consideration of Law No. 22 of 2009 on Traffic and Road Transport. Cases that often experience pros and cons in the field of law is a case related to negligence. The neglect is usually done by most people ie in the case of traffic accidents, the accident until the death of the victim. A frequent form of violation in traffic on the highway is a traffic accident. For example, running beyond the specified speed limit then tire broke that resulted in the vehicle having an accident. Based on the description above, the authors are interested to examine the problem with the title: